Glucose-Responsive Nanoparticles for Rapid and Extended Self-Regulated Insulin Delivery - Volpatti, Lisa R; Matranga, Morgan A; Cortinas, Abel B; Delcassian, Derfogail; Daniel, Kevin B; Langer, Robert; Anderson, Daniel G (ACS nano, 2020)
To mimic native insulin activity, materials have been developed that encapsulate insulin, glucose oxidase, and catalase for glucose-responsive insulin delivery. A major challenge, however, has been achieving the desired kinetics of both rapid and extended release. Here, we tune insulin release profiles from polymeric nanoparticles by altering the degree of modification of acid-degradable, acetalated-dextran polymers. Nanoparticles synthesized from dextran with a high acyclic acetal content (94% of residues) show rapid release kinetics, while nanoparticles from dextran with a high cyclic acetal content (71% of residues) release insulin more slowly. Thus, coformulation of these two materials affords both rapid and extended glucose-responsive insulin delivery. In vivo analyses using both streptozotocin-induced type 1 diabetic and healthy mouse models indicate that this delivery system has the ability to respond to glucose on a therapeutically relevant time scale. Importantly, the concentration of human insulin in mouse serum is enhanced more than 3-fold with elevated glucose levels, providing direct evidence of glucose-responsiveness in animals. We further show that a single subcutaneous injection provides 16 h of glycemic control in diabetic mice. We believe the nanoparticle formulations developed here may provide a generalized strategy for the development of glucose-responsive insulin delivery systems.